REPRESENTASI RELIGI DALAM NOVEL RINDU KARYA TERE LIYE - Mersa Aprilianie; Chelsy Yesicha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Novels are one of the literary works which contain life lessons, because basically literary works contain the teachings of aesthetic morals, and various things concerning the relationship of fellow human beings. One of the country’s most famous writers is Tere Liye with various best seller novels such as the Rindu novel that gets high enthusiasm from the readers. This novel entitled Rindu was awarded at the 2015 Islamic Book Award event. This is what makes the writer want to know “Religious representations in Rindu novels by Tere Liye”.Thid writing method is qualitative using narrative analysis Vladimir Propp. The subject of this research is the Rindu novel by Tere Liye. This research focuses on problems related to religious values. The way of data collection is done by dokumentation and literature study techniques. After collecting data, an analysis of the method of this research was conducted to obtain results.The results of this study indicate that the religious values obtained from the characters are several forms of religious value categories which include religious values in worshiping the God, which come from the highest truths that come from God and the vast scope of values and regulates all aspects of life human. Religious values in everyday life are based on courage, doing something by not worrying about possibilities and acting wisely to achieve something. Religious values in people’s lives are affection among others which makes the formation of an attitude of service, help, care and family.